Differential expression of Oct-4, CD44, and E-cadherin in eutopic and ectopic endometrium in ovarian endometriomas and their correlations with clinicopathological variables - Ceyda Sancakli Usta; Gulay Turan; Cagla Bahar Bulbul; Akin Usta; Ertan Adali (BMC, 2020)
Abstract Background Endometriosis is an estrogen-dependent inflammatory disease that often causes infertility and chronic pelvic pain. Although endometriosis is known as a benign disease, it has demonstrated characteristics of malignant neoplasms, including neoangiogenesis, tissue invasion, and cell implantation to distant organs. Octamer-binding protein 4 (Oct-4) is a molecular marker for stem cells that plays an essential role in maintaining pluripotency and self-renewal processes in various types of benign and malignant tissues. CD44 is a multifunctional cell surface adhesion molecule that acts as an integral cell membrane protein and plays a role in cell-cell and cell-matrix interactions. E-cadherin is an epithelial cell-cell adhesion molecule that plays important role in the modulation of cell polarization, cell migration, and cancer metastasis. The aim of this study was to investigate the expression patterns of Oct-4, CD44, and E-cadherin in eutopic and ectopic endometrial tissues from women with endometrioma compared to control endometrial tissues from women without endometrioma. Methods In the present study, Oct-4, CD44, and E-cadherin expressions were evaluated in eutopic and ectopic endometrial tissue samples from women with endometrioma (n = 32) and compared with those of control endometrial tissue samples from women without endometrioma (n = 30). Results Immunohistochemical expression of Oct-4 was significantly higher in the ectopic endometrial tissue samples of women with endometrioma than in the control endometrial tissue samples (p = 0.0002). Conversely, CD44 and E-cadherin expressions were significantly lower in the ectopic endometrial tissue samples of women with endometrioma than in the control endometrial tissue samples (p = 0.0137 and p = 0.0060, respectively). Correlation analysis demonstrated significant correlations between Oct-4 expression and endometrioma cyst diameter (p = 0.0162), rASRM stage (p = 0.0343), and total rASRM score (p = 0.0223). Moreover, CD44 expression was negatively correlated with the presence of peritoneal endometriotic lesions (p = 0.0304) while E-cadherin expression was negatively correlated with the presence of deep infiltrating endometriosis (p = 0.0445). Conclusions Increased expression of Oct-4 and decreased expression of adhesion molecules in endometriotic tissues may contribute to the development and progression of endometriosis.